The Allocation of Credit and Financial Collapse - Mankiw, N. Gregory (Quarterly Journal of Economics, 1986)
This paper examines the allocation of credit in a market in which borrowers have greater information concerning their own riskiness than do lenders. It illustrates that (1) the allocation of credit is inefficient and at times can be improved by government intervention, and (2) small changes in the exogenous risk-free interest rate can cause large (discontinuous) changes in the allocation of credit and the efficiency of the market equilibrium. These conclusions suggests a role for government as the lender of last resort.